Antibacterial effect of synthesized silver/montmorillonite nanocomposites by UV-irradiation method. - Ahmad, Mansor; Darroudi, Majid; Shameli, Kamyar; Abdullah, Abdul Halim; Ibrahim, Nor Azowa; Abdul Hamid, Azizah; Zargar, Mohsen (Medwell Journals, 2009)
Silver nanoparticles (Ag-NPs) were successfully synthesized into the interlayer space of Montmorillonite (MMT) by UV-irradiation method. AgNO3 and Montmorillonite (MMT) were used as a silver precursor and solid support, respectively. The properties of Ag/MMT nanocomposites were studied as a function of UV-irradiation time. UV-irradiation disintegrated the Ag NPs into smaller size until a relatively stable size and size distribution were achieved. The UV-vis spectra of synthesized Ag-NPs showed that the intensity of the maximum wavelength of the plasmon peaks increased with increasing UV-irradiation time. The synthesized Ag/MMT nanocomposites under longer UV irradiation time are very stable over a long time in aqueous solution without any sign of agglomeration or precipitants. The crystalline structure of the Ag-NPs and basal spacing of MMT and Ag/MMT were also studied by Powder X-Ray Diffraction (PXRD). The antibacterial activity of Ag-NPs was investigated against Gram-negative bacteria (Escherichia coli and Klebsiella pneumoniae) and Gram-positive bacteria (Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus (MRSA)) by disk diffusion method using Muller-Hinton Agar (MHA) at different sizes of Ag-NPs. All of synthesized Ag-NPs were found to have high antibacterial activity. These results showed that Ag-NPs can be useful in different biomedical research and applications such as diagnostic and surgical devices, contrast agents, drug delivery vehicles and physical therapy applications.